Parametric Study of Embankment Stability And Geotextile Reinforcement On Soft Soil - Alam, Mirza Syah; Wahyudi, Herman; Lastiasih, Yudhi; Kurniawan, Yusrizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The Semarang - Demak Toll Road Construction Project Section 1B has a length of 6.736 km, starting from STA. 1+578 to 8+314. There is a zone that has the highest embankment, namely zone N at STA. 4+200 to 4+600. However, based on soil investigation data, it is known that the Semarang - Demak Toll Road Construction Project Section 1B has a very thick compressible layer, which reaches a depth of 50 m. This makes the Semarang - Demak Toll Road Construction Project Section 1B face various challenges of construction on soft soil.The purpose of this research is to determine the Safety Factor (SF) value and the appropriate configuration of geotextile reinforcement requirements in an embankment with variations in compressible layer thickness, embankment height and embankment slope, especially in the case study of zone N with STA. 4+200 - 4+600. This research will be processed using the Limit Equilibrium Method (LEM) with the GEO5 auxiliary program.Based on the results in this study, it is known that the variation of compressible layer thickness does not have a significant influence on the calculation of the Safety Factor and geotextile reinforcement configuration. However, the variation of embankment height leads to the conclusion that the higher the embankment, the lower the Safety Factor. The variation of embankment slope also concluded that the steeper the embankment, the lower the Safety Factor. In addition, it is also known that the higher the embankment, the higher the number of geotextile reinforcement requirements and the steeper the embankment, the higher the number of geotextile reinforcement requirements. After making a nomogram of the relationship between these variations and implementing it on the case study, it is known that the embankment in Zone N of the Semarang - Demak Toll Road Construction Project Section 1B has a Safety Factor value of 0.42 and requires 33 layers of geotextile reinforcement with a tensile strength of 200 kN/m, a spacing of 25 cm between layers, and a Reduction Factor value of 1.65.